Position-specific differences in countermovement vertical jump force-time metrics in professional male basketball players - Cabarkapa, D.; Philipp, N. M.; Cabarkapa, D. V.; Fry, A. C. (Frontiers in Sports and Active Living, 2023)
The countermovement vertical jump (CVJ) is one of the most commonly implemented non-invasive and time-efficient testing modalities for lower-body neuromuscular performance assessment. With more practitioners having access to portable force plates, the purpose of this study was to examine position-specific differences in CVJ force-time metrics within a cohort of elite professional male basketball athletes. Twenty-eight athletes competing in top-tier European basketball leagues volunteered to participate in the present study. Following familiarization with testing procedures and a standardized warm-up protocol, each athlete performed three maximal-effort CVJ on a uni-axial force plate system with hands on the hips during the entire movement. To minimize the possible influence of fatigue, each jump trial was separated by an approximately 15-s rest interval. The mean value across three jumps was used for performance analysis purposes. The findings of the present study reveal notable position-specific differences during the eccentric phase of the CVJ, with centers having greater braking impulse, mean force, and mean power when compared to guards. However, when normalized by body mass, the observed differences during the eccentric phase of the CVJ were nonexistent. On the other hand, no significant differences in absolute mean and peak force and power were detected during the concentric phase of the CVJ. Yet, when normalized by the player`s body mass, centers demonstrated inferior performance than guards for the same force-time metrics. Overall, these findings may help practitioners obtain a better insight into position-specific differences with regards to CVJ force-time characteristics as well as aid with individually tailored training regimen design.